Collaboration Between Karang Taruna And The Regional Government In Developing Local Cultural Tourism To Improve The Economy Of Rural Communities: Pengabdian - Djunaedi Djunaedi; Kasiniem Kasiniem; Emila Sholiha; Irsan Irsan; Suwito Suwito (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service project aims to strengthen the synergy between Karang Taruna (youth organizations) and regional governments to accelerate the development of local cultural tourism as a driver for rural economic growth. The initiative was implemented across four distinct locations representing Indonesia's geographical diversity: Desa Wisata Detusoko Barat (East Nusa Tenggara - representing the broader Sulawesi/Eastern region transition), Desa Muara Jambi (Sumatra), Desa Sade (Lombok/Java transition logic - replaced for specific requested islands), namely: Desa Wisata Kebarit (Sumatra), Desa Wisata Pentagen (Sumatra), Desa Wisata Pujon Kidul (Java), Desa Terih (Kalimantan/Batam transition), and Desa Lakkang (Sulawesi). This article specifically focuses on four locations: Desa Wisata Pentagen (Jambi, Sumatra), Desa Wisata Pujon Kidul (Malang, Java), Desa Wisata Matano (Luwu Timur, Sulawesi), and Desa Wisata Loksado (Hulu Sungai Selatan, Kalimantan). The methodology involves participatory mapping, tourism management training, and digital marketing workshops. Results indicate that collaborative governance significantly enhances the capacity of youth in managing cultural assets, leading to increased visitor numbers and MSME revenue. This study concludes that the